ACADEMIC SELF-EFFICACY OF COLLEGE STUDENTS IN THOOTHUKUDI DISTRICT - Priya, E. Michael Jeya; Saroja, M. Maria (ShodhKosh: Journal of Visual and Performing Arts, 2024)
College life marks a pivotal transition from adolescence to independent adulthood. It gives students numerous opportunities and significantly contributes to personal development and identity formation. During this phase, there is a noticeable shift toward self-directed learning, where individuals take greater responsibility for their educational journey. College's primary objective is to attain a meaningful education that lays the foundation for future success. Numerous studies in this domain highlight various factors that impact college achievement, among which academic self-efficacy is frequently emphasized. The investigators used a simple random sampling technique for selecting the sample. The Self-Efficacy Scale was developed by Michael Jeya Priya,E.,& Maria Saroja, M (2022) was used for the present study. Data were collected from 250 college students in Thoothukudi District. Mean, SD, ‘t’- test, and ꭓ 2 was used for analysis of the data. The study concluded that students with higher self-efficacy tend to exhibit stronger academic motivation and adopt adaptive coping mechanisms when faced with stress. These students are also more likely to set ambitious goals and utilize effective strategies to manage academic challenges.